Board of Proprietors of the Eastern Division of New Jersey records - Board of Proprietors of the Eastern Division of New Jersey
Account book (1771 September 12-1843-July 11; 129 pages) relating chiefly to land transactions in eastern New Jersey and the internal business of the board. Many of the accounts relate to James Parker and Theophylact Bache. Also includes a volume recording "certificates of mislocation" (1789 April 17-1842 May 17).
Microfilm edition available
Microfilm produced from the originals in the Manuscript Division.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Parker, James, -- 1776-1868.; Bache, Theophylact, -- 1735-1807.; Land companies -- New Jersey